Profit Efficiency and Waste Management in Poultry Farming: The Case of Egba Division, Ogun State, Nigeria - Olumayowa, Oyebanjo; Abiodun, O. Otunaiya (International Journal of Poultry Science, 2011)
The study examined the profit efficiency and poultry waste management in Egba division of Ogun State, Nigeria. A sample of seventy-two (72) poultry farmers was randomly selected from the study area through structured questionnaires. The data analysis was based on complete responses from a cross-sectional survey of the respondents. The data were analyzed using frequency distribution and frontier profit function. Results showed that poultry production was dominated by males (84.7%) and majority (73.6%) was below 50 years of age. About 98.6% of the poultry farmers had minimum of primary education while 86.1% had less than 10 years of farming experience. 70.9% of the household had up to 6 members in their family while 29.1% had between 7-12 members. Statistics shows that 93.1% of the respondents collected their poultry waste manually using shovel and spade. Majority (76.39%) of the farmers did not treat their farm waste before or after disposal thereby polluting their environment. The poultry ‘waste’ was not considered useful by 63.9% of the farmers. However, the mean level of efficiency for poultry production in the area is 68.44 indicating that there is opportunity to still increase profit by 31.6% if technical, allocative and scale efficiencies are improved upon. Meanwhile, age, experience and sex significantly contributed to inefficiency in poultry farming in the area. It is therefore suggested that livestock farmers should be trained through workshops, conferences and extension services on the conversion and utilization of livestock waste or manure e.g. into organic fertilizers which can easily be made available to the numerous small scale crop farmers to augment the scarce and very expensive inorganic fertilizer. Effective monitoring services should be operated by government to sensitize poultry farmers to reduce environmental pollution and incidence of disease outbreak. Government should reduce import duties on poultry drugs so as to enhance increased production and profitability.